Association between physical activity, nutritional status and cognitive performance among school children in southern Tanzania - Fahad S. Mwakalebela; Fahad S. Mwakalebela; Elihaika G. Minja; Elihaika G. Minja; Elihaika G. Minja; Yohana A. Mwalugelo; Erick Killel; Erick Killel; Rehema K. Rajab; Rehema K. Rajab; Getrud J. Mollel; Getrud J. Mollel; et al. (Frontiers in Public Health)
BackgroundPhysical activity is pivotal in promoting overall health and wellbeing, improving brain function and cognitive performance, and reducing risk of excessive weight and non-communicable diseases. Despite these benefits, physical inactivity among children and adolescents remains a global concern, particularly in low- and middle-income countries (LMICs). Only few studies have explored the association between physical activity, nutritional status, and cognitive performance in LMICs like Tanzania. This study assessed these associations among school children in a rural setting in southern Tanzania.MethodsPhysical activity was assessed using an actigraphy device that assessed 7-day average of physical activity among school children aged 6–13 years. Cognitive performance was assessed via the Flanker task, which assessed the executive domain of cognitive functions, specifically information processing and inhibitory control. Weight was determined using Tanita digital scale, and height was measured using measuring board. A multinomial logistic regression model and a gamma generalized linear model with a log link function were used to examine the association between physical activity, nutritional status, and cognitive performance.ResultsAmong 678 children who participated in the baseline assessment, 77.9% had normal weight, 14.3% were underweight, 5.5% were overweight, and 2.4% were obese. Most (92.6%) of the children engaged in at least 60 min per day of moderate-to-vigorous physical activity (MVPA) as per WHO recommendations. Children who did not meet the recommended MVPA level were nearly three times more likely to be obese compared to those who did. No statistically significant associations were found between physical activity and cognitive performance, or between nutritional status and cognitive performance.ConclusionThis study highlights a high prevalence of normal weight and adherence to WHO-recommended MVPA levels among school children in southern Tanzania. However, children not meeting MVPA criteria were more likely to be obese, indicating the importance of physical activity in maintaining a healthy weight. The lack of association between physical activity or nutritional status and cognitive performance, indicates that there may be additional factors that influence cognitive outcomes. Further research is needed to explore these interactions, particularly in rural LMIC settings.